Analysis of stable isotope ratios in blood of tracked wandering albatrosses fails to distinguish a δ13C gradient within their winter foraging areas in the southwest Atlantic Ocean. (6th November 2015) - Ceia, Filipe R.; Ramos, Jaime A.; Phillips, Richard A.; Cherel, Yves; Jones, Daniel C.; Vieira, Rui P.; Xavier, José C.
Abstract : Rationale: The main limitation of isotopic tracking for inferring distribution is the lack of detailed reference maps of the isotopic landscape (i.e. isoscapes) in the marine environment. Here, we attempt to map the marine δ 13 C isoscape for the southwestern sector of the Atlantic Ocean, and assess any temporal variation using the wandering albatross as a model species. Methods: Tracking data and blood and diet samples were collected monthly from wandering albatrosses rearing chicks at Bird Island, South Georgia, during the austral winter between May and October 2009. The δ 13 C and δ 15 N values were measured by mass spectrometry in plasma and blood cells, and related to highly accurate data on individual movements and feeding activity obtained using three types of device: GPS, activity (immersion) loggers and stomach temperature probes. Results: The tracked birds foraged in waters to the north or northwest of South Georgia, including the Patagonian shelf‐break, as far as 2000 km from the colony. The foraging region encompassed the two main fronts in the Southern Ocean (Polar and Subantarctic fronts). The δ 13 C values varied by only 2.1 ‰ in plasma and 2.5 ‰ in blood cells, and no relationships were found between the δ 13 C values in plasma and the mean latitude or longitude of landings or feeding events of each individual. Conclusions: The failure to distinguish a major biogeographic gradient in δ 13 C values suggest that these values in the south Atlantic Ocean are fairly homogeneous. There was no substantial variation among months in either the δ 13 C or the δ 15 N values of plasma or blood cells of tracked birds. As birds did not show a significant change in diet composition or foraging areas during the study period, these results provide no evidence for major temporal variation in stable isotope ratios in consumer tissues, or in the regional marine isoscape in the austral winter of 2009. Copyright © 2015 John Wiley & Sons, Ltd.